I assert ownership of it: Repatronage intentions in wine tourism - Pé Curto, A.; Loureiro, S. M. C.; Guerreiro, J. (Anatolia, 2025)
The current research aims to examine (1) the influence of psychological ownership on fostering commitment, (2) the influence of commitment in predicting repatronage intentions, and (3) the effect of quality of alternatives on the relationship between commitment and repatronage intentions in the context of wine tourism. Data collected from 574 Spanish and Portuguese wine tourists were analysed using a partial least squares method. Findings show that investment of self and intimate knowledge positively and directly affects psychological ownership and indirectly affects commitment towards the winery. The quality of alternatives was found to moderate and weaken the relationship between commitment and repatronage intentions. Winery managers are advised to develop emotional commitment with tourists and continuously monitor competitive services.